1995
DOI: 10.1074/jbc.270.38.22190
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylgalactosamine (GalNAc) Transfer to the Common Carbohydrate-Protein Linkage Region of Sulfated Glycosaminoglycans

Abstract: During the course of a study to elucidate the role of modification of the common polysaccharide-protein linkage structure, GlcA␤1-3Gal␤1-3Gal␤1-4Xyl␤1-O-Ser, in biosynthetic sorting mechanisms of the different sulfated glycosaminoglycan chains, a novel N-acetylgalactosamine (GalNAc) transferase was discovered in fetal bovine serum. The enzyme catalyzed the transfer of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Liver Brain of ␣-GalNAcT, was not utilized as an acceptor for polymerization; this finding indicated that the addition of an ␣-GalNAc residue may serve as a stop signal that precludes further elongation of HS chains and of CS chains (25). Based upon these results, we speculated that EXTL2 negatively regulates GAG biosynthesis by adding a stop signal to a growing chain; thus, lack of EXTL2 might increase the amount of HS and CS.…”
Section: Embryonic Fibroblastsmentioning
confidence: 87%
“…Liver Brain of ␣-GalNAcT, was not utilized as an acceptor for polymerization; this finding indicated that the addition of an ␣-GalNAc residue may serve as a stop signal that precludes further elongation of HS chains and of CS chains (25). Based upon these results, we speculated that EXTL2 negatively regulates GAG biosynthesis by adding a stop signal to a growing chain; thus, lack of EXTL2 might increase the amount of HS and CS.…”
Section: Embryonic Fibroblastsmentioning
confidence: 87%
“…Chondroitin GalNAcT-2 is a unique ␤1,4-GalNAc transferase that utilizes the tetrasaccharide serine, GlcUA␤1-3Gal␤1-3Gal␤1-4Xyl␤1-O-Ser, from the linkage region as an acceptor substrate. Previously, when this compound was tested as an acceptor together with a sugar donor, UDP-GalNAc, to search for such GalNAcTs using fetal bovine sera or mouse mastocytoma cell extracts as the enzyme source, only ␣-GalNAc transferase activity was detected, resulting in the exclusive production of an ␣-GalNAc-capped pentasaccharide, GalNAc␣1-4GlcUA␤1-3Gal␤1-3Gal␤1-4Xyl␤1-O-Ser (27,40,41). Therefore, high expression of ␣-GalNAc transferase might have interfered with the identification of a ␤1,4-GalNAc transferase, such as chondroitin GalNAcT-2.…”
Section: Discussionmentioning
confidence: 99%
“…GlcUA␤1-3Gal␤1-O-C 2 H 4 NHCbz was also synthesized. 2 Chondro-hexasaccharide (GlcUA␤1-3GalNAc) 3 was prepared from chondroitin as previously described (27 Construction of a Soluble Form of the Novel Chondroitin GalNAcT-A cDNA fragment of a truncated form of the novel chondroitin GalNAcT lacking the first 36 N-terminal amino acids was amplified by reverse transcription PCR with total RNA derived from G361 human melanoma cells (ATCC CRL-1424) as a template using a 5Ј-primer (5Ј-CGCGGATCCTTGTTAGGCAAATACACATTAATAAG-3Ј) containing an in-frame BamHI site and a 3Ј-primer (5Ј-CGCGGATCCGTTTT-GTGGTTCATACAGTAACGC-3Ј) containing a BamHI site located 37 bp downstream from the stop codon. PCR was carried out with Pfu polymerase (Stratagene, La Jolla, CA) for 30 cycles of 94°C for 30 s, 55°C for 30 s, and 72°C for 120 s in 5% (v/v) dimethyl sulfoxide.…”
Section: Materials-udp-[u-mentioning
confidence: 99%
“…Asialo-ovine submaxillary mucin was obtained by treating ovine submaxillary mucin prepared according to Tettamanti and Pigman (18) with Arthrobacter ureafaciens sialidase (Nakarai Tesque, Kyoto, Japan). Chondro-hexasaccharide (GlcUA␤1-3GalNAc) 3 and chondro-octasaccharide (GlcUA␤1-3GalNAc) 4 were prepared from chondroitin as described previously (19). (GlcUA␤1-3GlcNAc) 5 was prepared from hyaluronan as described previously (20).…”
mentioning
confidence: 99%